How to capital struktur effect to profitability : Evidence Real estate Firm For years 2017-2018 - Andi Arman (Jurnal Economic Resource, 2021)
The purpose of this study is to test and analyze how the capital structure measured by using DER affects the profitability of companies engaged in real estate listed on the IDX during 2017-2018. This research is a causality study that will identify the causeand effect of the capital structure variable on company profitability. The population in this study, namely all real estate companies listed on the IDX, as many as 65, then those that meet the sample criteria are 42 companies taken based on purposivesampling criteria. Hypothesis testing is done using the SPSS for the windows 24.0 test tool. The results of the study indicate that the capital structure has a significant positive effect on company profitability. These results indicate that when there is an increase in debt use, there is an increase in the company's profitability. Companies with ownership conditions. Long-term debt is used for long-term funding to buy fixed assets of the company to increase its production and sales in the hope that the company can get more significant profits. Although there is interest that must be paid if the company chooses to finance with debt, the trade-off theory states that companies with high profitability will maximize their long-term debt because the interest expensearising from these debts can reduce taxes that the company's profitability will increase. In line with the data tested in this study, 9 of the companies optimize debt to increase the company's profitability.